2016
DOI: 10.1186/s12864-016-2664-8
|View full text |Cite
|
Sign up to set email alerts
|

The common stress responsive transcription factor ATF3 binds genomic sites enriched with p300 and H3K27ac for transcriptional regulation

Abstract: BackgroundDysregulation of the common stress responsive transcription factor ATF3 has been causally linked to many important human diseases such as cancer, atherosclerosis, infections, and hypospadias. Although it is believed that the ATF3 transcription activity is central to its cellular functions, how ATF3 regulates gene expression remains largely unknown. Here, we employed ATF3 wild-type and knockout isogenic cell lines to carry out the first comprehensive analysis of global ATF3-binding profiles in the hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 49 publications
6
85
0
Order By: Relevance
“…(i) The Atf3 gene is expressed at a low basal level, but its expression is greatly increased by a wide spectrum of stress signals (28). Intriguingly, by global analysis of ATF3-binding sites using ChIP-seq, Yan and colleagues (60) showed that ATF3 binds to a surprisingly large number of sites on the genome; furthermore, their data supported the idea that ATF3 "bookmarks" sites on the genome to allow rapid transcriptional response upon stress stimulation. (ii) Atf3 is an immediate-early gene (31), which has a hallmark of encoding transcription factors that regulate the expression of other transcription factor genes, resulting in a cascade of changes in transcriptional profile.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…(i) The Atf3 gene is expressed at a low basal level, but its expression is greatly increased by a wide spectrum of stress signals (28). Intriguingly, by global analysis of ATF3-binding sites using ChIP-seq, Yan and colleagues (60) showed that ATF3 binds to a surprisingly large number of sites on the genome; furthermore, their data supported the idea that ATF3 "bookmarks" sites on the genome to allow rapid transcriptional response upon stress stimulation. (ii) Atf3 is an immediate-early gene (31), which has a hallmark of encoding transcription factors that regulate the expression of other transcription factor genes, resulting in a cascade of changes in transcriptional profile.…”
Section: Discussionmentioning
confidence: 72%
“…S3D), i.e., ATF/CRE, AP-1, and closely related sites (29,60). We tested whether ATF3 binds to the Ccl2 promoter by ChIP assay and found consistent binding at the −2.3-kb site (Fig.…”
Section: Ptx Increases Cancer Cell Seeding But Decreases the Cytotoxicmentioning
confidence: 99%
“…Our analysis of metformin increased H3K27ac peaks showed enrichment for ATF3 binding motifs (Fig 4D). Interestingly, ATF3 was also recently shown to bind genomic sites enriched with EP300 and H3K27ac for transcriptional regulation [59]. Moreover, analysis of ATF3 marks unique to either the non-treated or metformin treated conditions were found to be overrepresented in differentially expressed H3K27ac peaks when compared to all H3K27ac peaks.…”
Section: Discussionmentioning
confidence: 99%
“…The consensus binding sites for transcription factors predicted to interact with these retroviral promoters have been previously described [53]. The consensus binding sites for ATF3, AhR/ARNT, COUPTF1, E2F1, ETF, ENKTF1, FOXP3, GATA family, GCF, HNF, HIF, NF-Y, RxRα, SRF, TCF-4E, and TRβ were obtained from [7490]. Only those sites with a maximum of one base pair deviation from the consensus binding sequence (or two for large hormonal response elements) were annotated on the target retroviral 3′ LTR.…”
Section: Methodsmentioning
confidence: 99%